2023
DOI: 10.1002/mds.29367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dihydropyridines on the Motor and Cognitive Outcomes of Patients with Parkinson's Disease

Abstract: A BS TRACT: Background: Dihydropyridines (DHPs) may have neuroprotective effects against Parkinson's disease (PD).Objective: This study investigated the effects of DHPs on nigrostriatal dopaminergic denervation and longitudinal motor and cognitive outcomes in PD. Methods: We classified 476 patients with drug-naive PD who had undergone dopamine transporter imaging into three groups. They were selected according to a prior diagnosis of hypertension and use of DHPs and were matched using propensity scores: patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…As shown in Table 2 , one study detected a protective role of CCB use on long-term cognitive outcomes of PD. 14 One study found an effect of CCB use on reducing the death risk of PD. 7 However, the other three studies failed to detect any impact of CCB use on the progression of PD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 2 , one study detected a protective role of CCB use on long-term cognitive outcomes of PD. 14 One study found an effect of CCB use on reducing the death risk of PD. 7 However, the other three studies failed to detect any impact of CCB use on the progression of PD.…”
Section: Resultsmentioning
confidence: 99%
“…We identified two studies reporting a positive effect of CCB use on the progression of PD. 7 , 14 Calcium interacts with α-synuclein and was a potential target for treating PD. 29 , 30 A study indicated that CCB could potentially prevent spine enlargement by inhibiting the hypersensitivity of the synapse to excitatory inputs in PD and, therefore, could be a candidate for treating levodopa-induced complications in PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased expression of Cav1.3 in the cerebral cortex of patients with early Parkinson's disease occurs before pathological changes, suggesting that calcium homeostasis disorders are not only a compensatory consequence of neurodegenerative processes [30], but also an early feature of Parkinson's disease. DHP antihypertensive drugs appear to be attractive agents for neuroprotective and preventive treatment of PD [31,32]. Epidemiological studies have shown that administration of DHP-type Ca 2+ channel blockers reduces the risk of PD in late life by 20 to 30% [33,34].…”
Section: Calcium and Pdmentioning
confidence: 99%